A idéia de posição original na teoria da justiça como eqüidade de John Rawls - Felipe, Rosane Terezinha (2008)
The objective of the present work consists in the investigation and exhibition of the conception of the original position in the theory of justice as fairness, drawn by John Rawls. For that, it is highlighted the way the author exhibits the agreement made in this initial situation of the choice, in other words, the parts symmetrically situated in the original position and covered by the veil of ignorance, that has the function to impede the passage of arbitrary information that can influence in the choice of the principles. Besides, the agreement made in the original position is characterized as hipothetical and non-historical. Rawls, in the subsequent works of A Theory of Justice, emphasizes that the misunderstanding about the hypothetical aspect of this position is due to the fact it isn´t seen as a representation artifice. By this way , in order to understand the argumentation about the original position, it treats the doctrines, in which the theory of justice as fairness, is presented as an alternative, with the intent to contextualize the theory of Rawls. From the works of the own author, it looks for presenting the fundamental ideas and the way how they are linked in this theory. Besides, they are object of study the role and the characteristics of this initial situation of the choice and the principles of justice, as the result of the agreement made between the parts in the original position, are objects of the study. This position is understood as an initial situation of the suitable equality for the choice of the principles, that must specify the fair terms of the society understood as a system of social cooperation.